2022
DOI: 10.22470/pemj.2022.00451
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 pandemic-related change in children’s visits to the emergency department

Abstract: Purpose: This study was performed to investigate the coronavirus disease 2019 pandemic-related changes in visiting pattern of an emergency department (ED).Methods: The author investigated all children younger than 19 years who visited the ED from 2018 through 2020 without exclusion criteria. Pandemic period was defined as 2020. Variables of interest were monthly and annual numbers of visits, age and age groups (< 1, 1-4, 5-9, 10-14, and 15-18 years), sex, visits for diseases, disposition, high acuity, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This study provides a nationwide analysis of pediatric ED use in Korea over a span of 5 years, from 2018-2022. Most ED visits were made by boys, with those aged 1-6 years being the most frequent visitors, a trend consistent with previous studies [5,8,11,[13][14][15][16][17]. During the preschool years, children in communal settings like daycare centers or kindergartens are easily exposed to respiratory and gastroenteritis viruses, facilitating the trans-mission of communicable diseases [18][19][20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study provides a nationwide analysis of pediatric ED use in Korea over a span of 5 years, from 2018-2022. Most ED visits were made by boys, with those aged 1-6 years being the most frequent visitors, a trend consistent with previous studies [5,8,11,[13][14][15][16][17]. During the preschool years, children in communal settings like daycare centers or kindergartens are easily exposed to respiratory and gastroenteritis viruses, facilitating the trans-mission of communicable diseases [18][19][20].…”
Section: Discussionsupporting
confidence: 87%
“…In pediatrics, diseases rather than injuries constitute a major reason for ED visits. This is consistent with previous studies [5,8,11,[13][14][15]17]. As depicted in Table 4, children primarily present to the ED with common symptoms like fever and abdominal pain rather than trauma.…”
Section: A a B Bsupporting
confidence: 92%
See 1 more Smart Citation
“…Kang 33 reported a decrease in ED patients during the implementation of SD measures during the global COVID-19 pandemic. Due to the lack of specialists and an increased risk of infection in EDs during the pandemic, specialists met with patients during specific times, and many patients avoided ED visits due to concerns about infection.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of specialists and an increased risk of infection in EDs during the pandemic, specialists met with patients during specific times, and many patients avoided ED visits due to concerns about infection. 33 34 35 36 The decrease in ED visits could also be attributed to the government’s policy of quarantining people at home to reduce the risk of COVID-19 transmission. In contrast, the number of suicide attempt patients increased post-SD, consistent with previous studies 30 31 that found an association between SD measures and mental health issues.…”
Section: Discussionmentioning
confidence: 99%